PERMIAN DEPOSITS IN THE NOVAYA ZEMLYA ISLANDS - Povysheva L.G.; Ustritskii V.I. (My University, 1996)
The Permian deposits of the whole Novaya Zemlya Archipelago are described for the first time. Five facies zones are distinguished and described. The age of brachiopod assemblages studied earlier was revised. Depositional environments are discussed. Distinctions are made between the formation of Permian deposits of Novaya Zemlya and the Ural Foredeep.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская